Оптимізація якісних характеристик поверхонь робочих деталей розділових штампів в умовах розмірної обробки електричною дугою - Шмельов, В. М.; Shmelyov, V. (КНТУ, 2014)
Виконано оптимізацію якісних характеристик поверхонь робочих деталей розділових штампів в умовах розмірної обробки електричною дугою (РОД). Показано залежність між конструкцією матриці і необхідною шорсткістю її робочої поверхні. Описано залежності якості обробленої поверхні робочих деталей розділових штампів від технологічних характеристик процесу РОД. The paper purpose-optimisation of qualitative performances of a surface of working details dividing ofstamps in the conditions of dimensional processing the electric arc. In a paper the analyzes of a construction of the matrix and a necessary surface roughness of working details of separating dies is carried out, on the basis of this gives recommended roughnesses of surfaces of working details received by methods of a classical electrical discharge machining. On the basis of experimental data derived the mathematical model of a surface roughness of working details dividing of stamps depending on the basic technical characteristics on process of dimensional processing the electric arc. It is shown that the surface roughness of working details dividing of stamps received by a mode of dimensional processing the electric arc, corresponds to the recommended surface roughness of these details received by classical methods of an electroerosion machining. Use of a mode of dimensional handling by an electric arc allows to receive working details of separating dies of the necessary sizes and with necessary indexes of a surface roughness of the worker of a part, and accordingly and to ensure necessary firmness, and lowering of the cost price of their manufacture. Using the method of dimensional processing the electric arc allows to receive of working details dividing of stamps the necessary sizes and with necessary indexes of a surface roughness of the worker of a part, and according to ensure necessary firmness, and lowering of the cost price of their manufacture.
Optimizing the quality characteristics of the surfaces working details dividing of stamps in the conditions dimensional processing the electric arc
Keywords: шорсткість; технологічний струм; статичний тиск потоку робочої рідини; матриця; пуансон; розділовий штамп; roughness; current technology; static pressure the working fluid flow; the matrix punch; dividing of stamp